RESISTANCE MECHANISMS OF Phaseolus acutifolius A. GRAY A Empoasca hraemeri ROSS AND MOORE (HOMOPTERA: CICADELLIDAE) - RODRIGUEZ, ADELA; MORALES, JUAN ANTONIO (Revista Colombiana de Entomología, 1990)
The mechanism of resistance to Empoasca kraemeri Ross and Moore in tepary beans, Phaseolus acutifolius A. Gray, were studied at CIAT (Palmira, Valle del Cauca, Colombia). Varieties studied were G40036, G40138, and G40128. These materials had been classified in previous studies as resistant, intermediate, and susceptible, respectively. Field studies pointed out indicated that tolerance is an important mechanism responsible for resistance in variety G40036, Feeding, and ovipositional preferences were detected in the susceptible variety G40128. Feeding preferences were not reconfirmed under greenhouse conditions. On the other hand, greenhouse studies reconfirmed ovipositional antixenosis in G40036 and ovipositional preferrence for the susceptible variety, G40128. None of the materials tested had antibiotic effects on eggs, nymphs, and adults of E. kraemeri. It is concluded that resistance of P. acutifolius to E. kraemeri is due to a combination of tolerance and ovipositional non preference mechanisms.